PERTANGGUNGJAWABAN HUKUM DALAM TRANSAKSI CROSS-BORDER E-COMMERCE STUDI KASUS SENGKETA KONSUMEN INTERNASIONAL - Imam Fathwa; Annie Myranika; Tri Susanto; Ratu Chumairoh Noor; Bayu Triwibowo (CV. Lafadz Jaya, 2026)
The development of information and communication technology has transformed the global trade landscape through the emergence of cross-border e-commerce. Cross-border electronic transactions provide convenience for consumers in accessing international products, but simultaneously create significant legal complexities, particularly regarding legal liability and consumer dispute resolution. This study analyzes international and national legal frameworks governing liability in cross-border e-commerce transactions, with specific focus on case studies of international consumer disputes. Using normative legal research methods with a comparative approach, this research examines international conventions, EU regulations, ASEAN frameworks, and Indonesian legislation. The results indicate complex jurisdictional challenges in determining applicable law and competent forums, exacerbated by information asymmetry and negotiation power gaps between consumers and businesses. This study recommends regional legal harmonization through effective Online Dispute Resolution (ODR) mechanisms and strengthening consumer protection based on consumer-priority jurisdiction principles to create legal certainty in cross-border e-commerce transactions.